Bilateral Hypotony Maculopathy Associated With Ipilimumab and Nivolumab Therapy Unresponsive to Corticosteroid Treatment - Ahmed, Abrahim A (Ophthalmic surgery, lasers & imaging retina, 2023)
In rare instances, immunotherapy associated with hypotony and uveitis has been documented. We report the case of a 72-year-old man treated with 2 months of ipilimumab and nivolumab for metastatic melanoma who developed bilateral hypotony maculopathy and serous choroidal detachments without prominent initial uveitis. Despite treatment with topical, periocular, and intraocular corticosteroid injection, hypotony persisted 18 months after immunotherapy cessation. The patient's unresponsiveness to corticosteroids indicates the need to further explore the mechanism behind immune checkpoint inhibitor-associated hypotony. We hypothesize that immunotherapy significantly decreased aqueous humor production through ciliary body inflammation, disruption, or shutdown. [Ophthalmic Surg Lasers Imaging Retina 2023;54:301-304.]